(−)‐Epigallocatechin gallate derivatives reduce the expression of both urokinase plasminogen activator and plasminogen activator inhibitor‐1 to inhibit migration, adhesion, and invasion of MDA‐MB‐231 cells. (16th July 2018) - Shin, Sunhye; Kim, Mi Kyoung; Jung, Woong; Chong, Youhoon
Abstract : Urokinase plasminogen activator (uPA) and its inhibitor plasminogen activator inhibitor‐1 (PAI‐1) are established independent biomarkers for high metastasis risk in breast cancer. In this study, we investigated the regulatory activity of (−)‐epigallocatechin‐3‐gallate (EGCG) and its derivatives on uPA and PAI‐1 expression and thereby their anti‐metastatic potential. EGCG showed only marginal effects on the uPA system and on the metastatic behavior of breast cancer cells (MDA‐MB‐231). However, the EGCG derivative3e with a methyl‐substituted carbonate substituent at the 4″‐position showed potent inhibition of PAI‐1 (62%) and uPA (50%) expression. The Ras‐extracellular‐signal‐regulated kinase (ERK), p38 mitogen‐activated protein kinase (MAPK), and phosphatidylinositol‐3‐kinase (PI3K)/Akt/NF‐κB pathways, which regulate uPA and PAI‐1 expression, were also affected by3e (25%, 45%, and 25% reduction, respectively). In line with these findings, substantial reduction in metastatic behavior of MDA‐MB‐231 cells, such as adhesion (40%), invasion (56%), and migration (40%), was observed in the presence of3e . It is also noteworthy that, in MDA‐MB‐231 cells, 3e did not exert any beneficial effect on the expression of matric metalloprotein (MMP) 2 and 9, which indicates that the anti‐metastatic activity of3e in MDA‐MB‐231 cells is not related to its regulation of the expression of MMPs. Taken together, we have shown that the EGCG derivative3e could suppress the metastatic behavior of MDA‐MB‐231 cells through regulation of uPA and PAI‐1.